SUPERVISION AND AUTOMATIZED CONTROL OF DRYING PROCESS THE AGRICULTURAL PRODUCTS THROUGH OF THE TERMICONT SOFTWARE - ROSA NETO, ALCEU; TERUEL, BÁRBARA (Revista Brasileira de Engenharia de Biossistemas, 2008)
Is presented the software TERMICONT, for supervision and control of a drying plant, monitor-ing the temperature and relative air humidity, rotation speed of the engine of the fan and energy consumption. The drying plant was instrumented with temperature sensor, relative humidity and active power. The applicatory one was developed in LabView 7.11; with man-machine interface and easy visualization, configuration of control type, curves of the system (open and closed loop), mathematical model and study of control strategies. The control supervisory one could be used as tool of remote and local performance (Web Lab), the air flow and power and simultaneously the heating resistance, acquisition and storage of process data. The plant will be used for the research in instrumentation application and control of processes and didactic tool for the practical lessons in the agricultural engineering course.